2017
DOI: 10.6007/ijarbss/v7-i10/3359
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Leverage and Profitability on Earnings Quality: Jordanian Case

Abstract: The fundamental target of financial accounting is to provide information helpful to investors in making forecasting about firms performance. The evolution of income reporting as the essential source for investor decision making has been well authenticated and income reporting helps economic society in a different ways. (Schroeder, et al., 2014) The present study aims to survey the influence of leverage measured by debt ratio separately on Earnings Quality, and the influence of profitability measured by retur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 1 publication
2
25
0
9
Order By: Relevance
“…Likewise, the results in a study of Warrad (2017) supported the causal link from return on asset as an indicator of financial performance to the quality of earnings; and another recent study took a similar line of thinking, revealing that companies with high financial performance more possibly satisfy their stakeholder's expectations without manipulating their true earnings (Du & Shen, 2018). However, the quality of earnings goes after the financial performance and is a driver of future organizational reputation (Hammond & Slocum, 1996).…”
Section: Organizational Reputation Organizational Reputationmentioning
confidence: 73%
See 2 more Smart Citations
“…Likewise, the results in a study of Warrad (2017) supported the causal link from return on asset as an indicator of financial performance to the quality of earnings; and another recent study took a similar line of thinking, revealing that companies with high financial performance more possibly satisfy their stakeholder's expectations without manipulating their true earnings (Du & Shen, 2018). However, the quality of earnings goes after the financial performance and is a driver of future organizational reputation (Hammond & Slocum, 1996).…”
Section: Organizational Reputation Organizational Reputationmentioning
confidence: 73%
“…The interplay between the quality of publicly disclosed earnings and financial performance or value has broadly been discussed in previous research (e.g. Latif et al, 2017;Warrad, 2017;Huynh, 2018;Du & Shen, 2018). Those scholars have only focused on the causal interactions from the quality of earnings to financial performance or in the opposite influential direction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Pakistan, (Bhatti, 2011) revealed that the level of debt would encourage profitability. Meanwhile, in a study at the Amman Stock Exchange, Jordan, by (Warrad, 2017) also showed the effect of ratio of leverage debt on the profitability of industrial companies. However, research in Thailand by (Vithessonthi and Tongurai, 2015) leverage caused different influences on small and large firms where the small firms were negatively influenced and large companies vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the earnings quality becomes important. Earnings quality is an indicator of earnings disclosure ability to predict cash flow in the future (Penman, 2001;Warrard, 2017). Low earnings quality means that earnings can not accurately predict future cash flows.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%